The Reflection Quadrant. A way to guide reflection - Mart Ottenheim (European Teacher Education Network, 2014)
In a changing world were the Internet and computers play an important role in de lives of many students, a teacher should change his ways of teaching by using these new technologies. Those are not the only changes a teacher should adapt to. Culture changes, relations between men and women change, economics and jobs change and most important, the way children learn change. The teacher must be able to constantly follow these technological and social changes and adapt his/her teaching accordingly. This can be done passively, slowly changing with the flow but it is much more effective to react to the changes in an active manner by reflection on once own actions (Schön, 1983). Several ways of reflection can be categorised (Pinsky et al., 1998): anticipatory reflection, reflection-‐in-‐action and reflection-‐on-‐action (Shulman, 1987; Irby, 1992; Schön, 1983; Eraut, 1994). Anticipatory reflection is done prior to an action. Reflecting-‐ in-‐action is done during teaching, seeing ones own actions and acting in response to it. Reflection-‐on-‐action is done after the action; looking back on the experience and trying to learn from it. The growing importance of reflection in education is part of a changing paradigm from knowledge based action to experienced based action (Boud, 1999).